The occupation of justice Supreme Court of Israel and the Occupied Territories - Kretzmer, David 1943-; 1968- (SUNY series in Israeli studies, 2021)
This book is an updated and expanded study of the manner in which the Supreme Court of Israel has related to petitions challenging actions of the Israeli authorities in the territories occupied by Israel during the 1967 War. The first edition of the study was published two decades ago by one of the present authors, David Kretzmer. The original work was completed just before the second intifida began in September 2000. It covered decisions of the Supreme Court both during the formative years of the Court's jurisprudence on the occupation, and during the first intifada that broke out in December 1987. As stated in the preface to the first edition, the beginning of the second intifada proved that the hopes that the historic Oslo Accords between Israel and the PLO (1993-1995) would lead to peace between Israel and the Palestinians and to the end of the occupation were premature. At the present time (2020) an end to direct Israeli control over the West Bank and restrictions on life in Gaza does not seem to be in sight. The so-called peace plan published by the Trump Administration in February 2020, as we were completing the manuscript, does not alter that picture, although it may contribute to changes in the regime in the West Bank. Much that has happened since the first edition was published has affected the type of cases that reach the Supreme Court, and consequently the topics covered in this study. After a wave of suicide bombings in Israel in 2001 and 2002 the IDF embarked on a military operation in the West Bank. This operation and subsequent hostilities between the IDF and armed Palestinian groups yielded a host of petitions relating to means and methods of warfare and to judicial review during active hostilities. In 2002 the Israeli government began the construction of a separation barrier in the West Bank, the declared purpose of which was to make it more difficult for potential Palestinian terrorists to enter Israel itself. The barrier's route not only spurred close to two hundred petitions to the Supreme Court; it was also the subject of an advisory opinion by the International Court of Justice. In August 2005 Israel withdrew its armed forces and civilian settlements from the Gaza Strip under the Disengagement Plan, and the government announced that Israel no longer had responsibility for Gaza. Controversy arose whether Gaza remained occupied territory. In 2006 the Hamas movement gained control over Gaza and the Government of Israel declared Gaza to be 'hostile territory.' The relations between Israel and Gaza have been tense ever since, with firing of rockets and bombs on Israeli towns and villages, severe restrictions on supply of goods to Gaza and movement of people between Gaza and the West Bank, and periods of active hostilities between Israel and Gaza. Since the first edition of this study was completed there has been a dramatic expansion in the number of Israeli settlements and settlers in the West Bank. This expansion has had various legal and practical consequences, including the emergence of two different legal regimes applicable to Israelis and to Palestinians resident in the West Bank"--